(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In the world today, in order to replace lost natural teeth with artificial teeth, to prevent infectious inflammations after implant placement, treatment using mechanical methods is considered one of the urgent issues. An implant is an artificial root in the form of a titanium screw, which is surgically placed in the jawbone. The crown of the tooth is then attached to replace the missing tooth. This is the most effective way to replace a missing tooth.